2014
DOI: 10.1097/iae.0b013e31829f7495
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intravitreal Dexamethasone Implant (Ozurdex) on Macular Morphology and Function

Abstract: In eyes with macular edema secondary to central retinal vein occlusion, intravitreal dexamethasone provides functional benefits that correlate well with ultrastructural macular changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
5
24
1
Order By: Relevance
“…This compares favourably with results from the GENEVA trial, which showed a mean reduction of 119µm at 180 days following treatment [9], as well as other studies [14,18,19]. However there was no association between change in VA and change in CRT following treatment in our study, regardless of the baseline VA. As improvement in CRT does not necessarily reflect visual improvement, we surmise that resolution of ME on OCT scanning may leave residual macular atrophy or scarring with consequently little improvement in VA.…”
Section: Anatomical Outcomessupporting
confidence: 69%
“…This compares favourably with results from the GENEVA trial, which showed a mean reduction of 119µm at 180 days following treatment [9], as well as other studies [14,18,19]. However there was no association between change in VA and change in CRT following treatment in our study, regardless of the baseline VA. As improvement in CRT does not necessarily reflect visual improvement, we surmise that resolution of ME on OCT scanning may leave residual macular atrophy or scarring with consequently little improvement in VA.…”
Section: Anatomical Outcomessupporting
confidence: 69%
“…Several studies reported its efficacy in decreasing CRT and improving visual function in RVO eyes [11,12,13,14,15]. However, the mechanism by which dexamethasone and other steroids reduce macular edema in RVO and the exact time course of drug action are not fully recognized yet.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, very little data are available to date. More specifically, the earliest SD-OCT information present in the literature describes the outcomes 1 month after treatment and shows a mean reduction of CRT between 150 and 300 μm [11,12,13]. In the present study we performed a sequential series of SD-OCT evaluations at 1, 2, 3, 7, 21, 28, 60, and 90 days after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further ‘real-life' studies describing series of patients treated with Ozurdex for ME due to RVO in multicentric or single-center institutional settings have found clinically meaningful benefits and no serious adverse events [10,11,12,13,14,15,16,17,18]. However, 12-month clinical data have rarely been reported in the previous literature nor has analysis on treatment-naïve eyes with recent onset disease.…”
Section: Introductionmentioning
confidence: 92%